An Overview of Pickering Emulsions: Solid-Particle Materials, Classification, Morphology, and Applications - Yang, Yunqi; Fang, Zhiwei; Chen, Xuan; Zhang, Weiwang; Xie, Yangmei; Chen, Yinghui; Liu, Zhenguo; Yuan, Weien (Frontiers in Pharmacology, 2017)
Pickering emulsion, a kind of emulsion stabilized only by solid particles locating at oil-water interface, has been discovered a century ago, while being extensively studied in recent decades. Substituting solid particles for traditional surfactants, Pickering emulsions are more stable against coalescence and can obtain many useful properties. Besides, they are more biocompatible when solid particles employed are relatively safe in vivo. Pickering emulsions can be applied in a wide range of fields, such as biomedicine, food, fine chemical synthesis, cosmetics and so on, by properly tuning types and properties of solid emulsifiers. In this article, we give an overview of Pickering emulsions, focusing on some kinds of solid particles commonly serving as emulsifiers, three main types of products from Pickering emulsions, morphology of solid particles and as-prepared materials, as well as applications in different fields.